Kaip namie (Just like at home): Sociolinguistic Interpretation of the Phraseological Idiom - Župerka, Kazimieras (Acta humanitarica academiae Saulensis, 2019)
Phraseological comparison kaip namie (Just like at home) is used whilst selfexplaining the local as well as spiritual (emotional) self-knowledge in the place that you are: do you feel like you are at home, just like home or do you feel foreign. The most important aspects of “home” are place, people, language and culture. The concept of “home” could be constructed from one or a few of the aspects, their harmony. The phraseological comparison implicates complicated semantics: first of all, from the adverb namie “at home”, we can apprehend that we are talking about a specific (physical, real, or abstract, imaginary, unreal) place, space; second, this adverb connected with the conjunction kaip “like” can show that we are talking about not-home – place which only from a certain angle can resemble home. In dictionaries, this phraseological definition can be found: “[to feel] good, free”. Context clues show that speakers are fond of the “comfortable, secure” meaning. In addition, context clues can display that some speakers (even from the younger generation) could associate the phraseological idiom kaip namie with a certain physical place, relatives, native language and even with the whole existence (of all the circumstances); others (especially younger ones) already have the cosmopolitan self-knowledge: they insist that they can feel like being at home anywhere. Academics of culture, sociologists assert that a modern person would more often search for home in culture and in a way is trying to bring back something that is slowly becoming foreign, changing substantial reality to circumstantial one. A very clear illustration of these points can be seen in the sculptor Antanas Šnaras’ phraseological sculpture-installation “Kaip namie”; in 2008, this gigantic, almost a meter and a half, in granite letters “written” phrase was placed in various squares of Vilnius for a brief moment.